Vision-related quality of life impact of refractive correction among myopes in Kelantan - Muzir, Nur Solehah; Ab Halim, Noorhazayti; Mohamad Zailani, Imtiyaz Syaddad; Ghosh, Somnath; Md Mustafa, Md Muziman Syah (Semarak Ilmu Publishing, 2026)
Uncorrected refractive errors, particularly myopia, can significantly affect an individual's vision-related quality of life (VRQoL). While refractive correction with spectacles or contact lenses is common, its actual impact on patients’ functional and emotional well-being remains underexplored. This study aimed to evaluate the VRQoL of myopic individuals using their current refractive correction. A cross-sectional study was conducted at four optometry practices in urban and suburban areas of Kelantan, Malaysia. A totalof 54 myopic participants aged 18 to 39 years were recruited through convenience sampling. Participants completed the validated Malay version of the Qualityof Life Impact of Refractive Correction questionnaire. Overall and emotional VRQoL scores were derived and analysed. Results showed that the magnitude of refractive correction significantly influenced overall VRQoL, with participants wearing correction of spherical equivalent refraction (SER) ≥ 3.00 D reporting lower overall VRQoL scores than those with SER < 3.00 D. Age and gender significantly influenced emotional VRQoL, with males and the middle-aged adult group of 30 to 39 years reporting better emotional well-being. In conclusion, specific demographic and refractive correction characteristics impact overall and emotional aspects of VRQoL. These findings underscore the need for personalised optometric care and support systems that address not only refractive correction but also psychological well-being in myopic patients.